Institutional Frameworks, Experience with CGIAR reform - Le Page, Lloyd (CGIAR Consortium, 2011)
Presentation by Lloyd Le Page, CEO of the CGIAR Consortium. It was a keynote address made during the OECD Conference on Agricultural Knowledge Systems, Responding to Global Food Security and Climate Change Challenges in Paris, 15-17 June 2011.